Porous Graphene Oxide Decorated Ion Selective Electrode for Observing Across-Cytomembrane Ion Transport - Shihui Hu; Rong Zhang; Yunfang Jia (Sensors, 2020)
The technology for measuring cytomembrane ion transport is one of the necessities in modern biomedical research due to its significance in the cellular physiology, the requirements for the non-invasive and easy-to-operate devices have driven lots of efforts to explore the potential electrochemical sensors. Herein, we would like to evidence the exploitation of the porous graphene oxide (PGO) decorated ion selective electrode (ISE) as a detector to capture the signal of cytomembrane ion transport. The tumor cells (MDAMB231, A549 and HeLa) treated by iodide uptake operation, with and without the sodium-iodide-symporter (NIS) expression, are used as proofs of concept. It is found that under the same optimized experimental conditions, the changed output voltages of ISEs before and after the cells’ immobilization are in close relation with the NIS related ion’s across-membrane transportation, including I−, Na+ and Cl−. The explanation for the measured results is proposed by clarifying the function of the PGO scaffold interfacial micro-environment (IME), that is, in this spongy-like micro-space, the NIS related minor ionic fluctuations can be accumulated and amplified for ISE to probe. In conclusion, we believe the integration of the microporous graphene derivatives-based IME and ISE may pave a new way for observing the cytomembrane ionic activities.